2017
DOI: 10.1021/acs.jmedchem.7b00425
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Potent and Selective Small-Molecule Reversible Factor D Inhibitors Demonstrating Alternative Complement Pathway Inhibition in Vivo

Abstract: The highly specific S1 serine protease factor D (FD) plays a central role in the amplification of the complement alternative pathway (AP) of the innate immune system. Genetic associations in humans have implicated AP activation in age-related macular degeneration (AMD), and AP dysfunction predisposes individuals to disorders such as paroxysmal nocturnal hemoglobinuria (PNH) and atypical hemolytic uremic syndrome (aHUS). The combination of structure-based hit identification and subsequent optimization of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Lorthiois et al [ 120 ] reported the synthesis of a novel series 1 H -indazole hybrids and investigated their potencies of factor D (FD). During the optimization, compound 198 showed more potent inhibitory activity against FD with an IC 50 value of 0.006 μM in the in vitro membrane attack complex (MAC) deposition assay ( Figure 70 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…Lorthiois et al [ 120 ] reported the synthesis of a novel series 1 H -indazole hybrids and investigated their potencies of factor D (FD). During the optimization, compound 198 showed more potent inhibitory activity against FD with an IC 50 value of 0.006 μM in the in vitro membrane attack complex (MAC) deposition assay ( Figure 70 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…It is usually initiated by C3 convertase to cleave complement C3 into C3a and C3b. Both C3 and C5 convertases play a vital role in forming the final product membrane attack complex (MAC) and cell lysis 20Figure 2Flow diagram shows three separate complement pathways: lectin pathway, alternative pathway and classical pathway (orange box).…”
Section: Introductionmentioning
confidence: 99%
“…Loch-Wilkinson et al identified 38 BI-ALCL cases in total (cases were divided into three different implant types) between 1999 and 2015. Using the reported incidence rates of the implant types gives a total of 1,345,563 implant years and represents an incidence rate of 28.2 (95%-CI: 20-38.8) per 1,000,000 implant years [23].…”
Section: Incidence In Comparison Studiesmentioning
confidence: 99%
“…Med. 2020, 9, 1247 6 of 10 a total of 1,345,563 implant years and represents an incidence rate of 28.2 (95%-CI: 20-38.8) per 1,000,000 implant years [23].…”
Section: Incidence In Comparison Studiesmentioning
confidence: 99%